PEM electrolyzed water non-fluorine proton exchange membrane and preparation method thereof

By preparing non-fluorine proton exchange membranes, the problems of high cost of commercial proton exchange membranes and incompatibility with the support layer and resin interface are solved, the performance improvement and cost reduction of PEM electrolytic cells are achieved, and the commercial application of PEM hydrogen production technology is promoted. .

CN119194510APending Publication Date: 2024-12-27SHENZHEN SENERGY FUEL CELL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411386637.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the existing PEM electrolytic hydrogen production technology, commercial proton exchange membranes are mainly perfluorosulfonic acid structures, which are expensive and the support layer is incompatible with the resin interface, resulting in high equipment costs, insufficient performance and durability, affecting the commercialization of the technology. .

Method used

Using the preparation method of a non-fluorine proton exchange membrane, the pretreated polyether ether ketone resin is mixed with cerium salt and solvent in a specific proportion to form a slurry and bonded with a support layer to prepare excellent mechanics by coating and drying. and electrochemical properties of PEM electrolytic water with non-fluorine proton exchange membrane.

Benefits of technology

The prepared non-fluorine proton exchange membrane has good stability and mechanical properties, which significantly improves the pressure resistance and polarization performance of the PEM electrolytic cell, reduces production costs, and has good compatibility with the interface of the support layer and resin, which is suitable for scale. Chemical production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005071107930000011
    Figure HDA0005071107930000011
  • Figure HDA0005071107930000012
    Figure HDA0005071107930000012
Patent Text Reader

Abstract

The invention discloses a preparation method of a non-fluorine proton exchange membrane for PEM electrolyzed water, which comprises the following steps: S01, adding pretreated resin into an acid solution for reaction to obtain a product mixed solution; s02, adding the product mixed solution in the step S01 into ice water while stirring, filtering, taking filter residues, washing and drying to obtain a product; s03, mixing a product obtained in the step S02, cerium salt and a solvent, stirring, and performing ultrasonic treatment to obtain slurry; s04, the surface of a carrier is coated with part of the slurry obtained in the step S03, and coating slurry is obtained; uniformly covering the coating slurry with a supporting layer, and drying to obtain supporting slurry; and S05, coating the residual slurry in the step S03 on the supporting slurry in the step S04, drying, and then drying to obtain the non-fluorine proton exchange membrane for PEM electrolyzed water. The method is low in production cost and can be used for large-scale production. The prepared proton membrane has better gas permeation barrier performance, and can meet the use requirements of fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a non-fluorine proton exchange membrane for PEM water electrolysis and a preparation method thereof. Background Art

[0002] Unlike alkaline water electrolysis hydrogen production technology, PEM water electrolysis (Proton Exchange Membrane Water Electrolyzers, PEMWE, proton exchange membrane water electrolysis) hydrogen production technology uses proton exchange membrane as a solid electrolyte to replace the diaphragm and liquid electrolyte (30% potassium hydroxide solution or 26% sodium hydroxide solution) used in alkaline electrolyzers, and uses pure water as the raw material for water electrolysis hydrogen production, avoiding potential alkaline solution pollution and corrosion problems. When the PEM electrolyzer is in operation, water molecules undergo oxidation reaction on the anode side, lose electrons, and generate oxygen and protons; then, electrons are transferred to the cathode through an external circuit, and protons are conducted to the cathode through the proton exchange membrane under the action of the electric field, and a reduction reaction occurs on the cathode side to obtain electrons to generate hydrogen. The hydrogen and oxygen after the reaction will be collected and transported through the bipolar plates of the anode and cathode.

[0003] Compared with alkaline water electrolysis hydrogen production technology, PEM water electrolysis hydrogen production technology has the advantages of high current density, high hydrogen purity, and fast response speed. The current density of PEM electrolyzer is usually 10000A / m 2 The purity of hydrogen produced is usually around 99.99%. Since the PEM electrolyzer uses pure water as the electrolysis raw material, the generated hydrogen will not bring in alkaline mist, which is beneficial to improving the quality of hydrogen. In addition, the gas permeability of the proton exchange membrane is low, which helps to avoid the cross-permeation of hydrogen and oxygen. The PEM electrolyzer does not need to strictly control the pressure on both sides of the membrane, has the advantages of fast start-stop and fast power regulation response, and is suitable for the fluctuating input of renewable energy power generation.

[0004] However, since PEM electrolyzers need to operate in a highly acidic and highly oxidizing working environment, the equipment is more dependent on expensive precious metal materials such as iridium, platinum, and titanium, resulting in high equipment costs for current PEM water electrolysis hydrogen production technology. The unit cost of PEM electrolyzers is still much higher than that of alkaline electrolyzers, and performance and durability need to be improved. Moreover, existing commercial proton exchange membranes are mainly perfluorosulfonic acid structures, which are not only expensive and complex to prepare, but also environmentally unfriendly because they contain fluorine. In addition, in addition to pure resin structures, current commercial proton exchange membranes also contain structures with support layer reinforcements, which have the problem of incompatibility between the support layer material and the perfluorosulfonic acid resin interface. Summary of the invention

[0005] The embodiment of the present invention provides a non-fluorine proton exchange membrane for PEM water electrolysis and a preparation method thereof, aiming to solve the problems of existing commercial PEM mainly based on perfluorosulfonic acid resin structure, high price, incompatibility between support layer and resin interface, etc.

[0006] In order to solve the above technical problems, the present invention first provides a method for preparing a non-fluorinated proton exchange membrane for PEM water electrolysis, comprising the following steps:

[0007] S01, adding the pretreated resin into the acid solution, reacting at 30°C to 80°C for 0.5h to 8h to obtain a product mixed solution;

[0008] S02, adding the product mixture of step S01 into ice water while stirring, filtering, taking the filter residue, washing and drying to obtain the product (sulfonated polyetheretherketone, SPEEK);

[0009] S03, mixing the product of step S02, cerium salt and solvent, stirring for 1h to 24h and then ultrasonicating for 1h to 8h to obtain a slurry; the mass ratio of the product, the cerium salt and the solvent is 1:(0.01-0.2):9;

[0010] S04, coating part of the slurry in step S03 on the surface of the carrier to obtain a coating slurry; uniformly covering the support layer on the coating slurry, and drying at 40° C. to 100° C. for 0.5 h to 24 h to obtain a support slurry;

[0011] S05, coating the remaining slurry of step S03 on the supporting slurry of step S04, drying at 40°C to 100°C for 0.5h to 24h, and then drying at 120°C to 200°C for 10min to 60min to obtain a non-fluorine proton exchange membrane for PEM water electrolysis.

[0012] As a preferred embodiment, in step S01,

[0013] The pretreated resin is pretreated by the following method: the resin is placed at 80° C. and dried for 24 hours under vacuum conditions to obtain the pretreated resin.

[0014] The mass ratio of the pretreatment resin to the acid solution is 1:(10-50).

[0015] The resin is polyetheretherketone (PEEK) resin.

[0016] The molecular weight of the polyetheretherketone resin is 1000-50000, preferably 4000-21800.

[0017] The drying is preferably carried out in an oven.

[0018] The acid solution is 98wt.% concentrated sulfuric acid.

[0019] The reaction is preferably carried out under stirring, and the stirring frequency is 500 rpm to 1000 rpm.

[0020] The reaction is preferably carried out at 40°C to 70°C for 1 h to 6 h.

[0021] As a preferred embodiment, in step S02,

[0022] The stirring speed is preferably 100 rpm to 400 rpm.

[0023] The washing was performed by washing with pure water several times until the mixture became neutral.

[0024] As a preferred implementation, in step S03,

[0025] The cerium salt is preferably one or a mixture of at least two of cerium nitrate, cerium dioxide, cerium chloride and cerium sulfate.

[0026] The solvent is preferably one of methanol, ethanol, n-propanol, isopropanol, deionized water, acetone, DMAc or DMF, or a mixture of at least two thereof.

[0027] The stirring time is preferably 2 h to 23 h; the ultrasonic time is preferably 2 h to 6 h.

[0028] As a preferred implementation, in step S04,

[0029] The coating thickness is 10 μm to 400 μm, preferably 20 μm to 280 μm. In the present application, coating is achieved by a coater.

[0030] The carrier is glass.

[0031] The support layer is a porous film with a thickness of 5 μm to 50 μm. When covering, the porous film can be stretched through the frame to ensure that the porous film is flat, so that it can be evenly covered on the coating slurry, thereby ensuring that the coating slurry can fully infiltrate the porous film.

[0032] The component of the support layer is preferably one or a mixture of at least two of expanded porous polytetrafluoroethylene, ultrafine polyetheretherketone fiber woven mesh, expanded porous polybenzimidazole, expanded porous polyethylene, expanded porous polyetheretherketone, expanded porous polystyrene, artificial graphite or expanded porous polyethyleneimine.

[0033] The drying is preferably carried out at 50° C. to 90° C. for 2 h to 20 h; the drying is achieved by using a forced air drying oven.

[0034] As a preferred embodiment, in step S05,

[0035] The coating thickness is 10 μm to 400 μm, preferably 20 μm to 280 μm. In the present application, the coating is achieved by a coater. In the embodiment of the present application, the coating thickness in step S04 is the same as the coating thickness in step S05, which can better ensure the good performance of the prepared proton membrane.

[0036] The drying is preferably carried out at 50° C. to 90° C. for 2 h to 20 h; the drying is preferably carried out at 130° C. to 180° C. for 15 min to 50 min; the drying and the drying are both carried out in a blast drying oven.

[0037] On the other hand, an embodiment of the present application further provides a non-fluorine proton exchange membrane for PEM water electrolysis, and the non-fluorine proton exchange membrane for PEM water electrolysis is prepared by the above-mentioned preparation method.

[0038] Compared with the prior art, the technical solution of the embodiment of the present invention has the following beneficial effects: the present application prepares a slurry by using SPEEK, cerium salt and solvent and controlling the ratio of the three, and then uses the slurry and the support layer to prepare a non-fluorine proton exchange membrane for PEM water electrolysis, so that the prepared non-fluorine proton exchange membrane for PEM water electrolysis (enhanced) has good stability and excellent mechanical properties and electrochemical properties; the non-fluorine proton exchange membrane for PEM water electrolysis is applied to PEM water electrolysis, which can effectively improve the pressure resistance of the PEM electrolyzer and significantly improve the polarization performance of the PEM electrolyzer. The preparation method of the present application is simple, easy to implement, low in production cost, high in production efficiency, and can be used for large-scale production. The prepared non-fluorine proton exchange membrane for PEM water electrolysis has better gas permeability barrier performance, and its support layer has good compatibility with the SPEEK resin interface, which can meet the use needs of fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0040] Figure 1 This is a schematic cross-sectional view of a non-fluorinated proton exchange membrane for PEM water electrolysis according to Example 1 of the present invention;

[0041] Figure 2 This is a schematic diagram of an electron microscope cross section of the proton exchange membrane of Comparative Example 1.

[0042] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0045] At present, PEM water electrolysis hydrogen production technology still has the problem of high cost, and its performance and durability need to be improved, which is not conducive to the improvement of its commercialization.

[0046] The present application prepares a slurry by using SPEEK, cerium salt and solvent and controlling the ratio of the three, so that the prepared non-fluorine proton exchange membrane for PEM water electrolysis has good compactness and better gas permeability barrier performance. The high proton conductivity brought by the high IEC (ion exchange capacity) of SPEEK can effectively provide excellent performance for the non-fluorine proton exchange membrane for PEM water electrolysis. At the same time, the use of a support layer for enhancement will further improve the stability of the non-fluorine proton exchange membrane for PEM water electrolysis (effectively making up for the lack of stability of the high sulfonation degree SPEEK membrane: high IEC will cause the SPEEK resin to have too high a sulfonic acid group density, excessive hydrophilicity and excessive swelling, affecting the structural stability of the proton membrane). The non-fluorine proton exchange membrane for PEM water electrolysis prepared by the present application based on SPEEK resin (i.e., a support layer enhanced proton membrane) can solve the problems of high cost of existing commercial proton membranes, incompatibility between the support layer material and the interface of the perfluorosulfonic acid resin, and further promote the large-scale commercial application of PEM hydrogen production technology. In the embodiments of the present application, the solution of the present application can be realized by controlling the operating conditions and the amount of raw materials used within the above ranges.

[0047] Example 1

[0048] A method for preparing a non-fluorine proton exchange membrane for PEM water electrolysis comprises the following steps:

[0049] S01, adding the pretreated resin to the acid solution, reacting at 80° C. for 0.5 h, to obtain a product mixed solution; the mass ratio of the pretreated resin to the acid solution is 1:20;

[0050] S02, adding the product mixture of step S01 into ice water while stirring, filtering, taking the filter residue, washing and drying to obtain the product (sulfonated polyetheretherketone, SPEEK);

[0051] S03, mixing the product of step S02, cerium salt and solvent, stirring for 1 hour and then ultrasonicating for 1 hour to obtain a slurry; the mass ratio of the product, the cerium salt and the solvent is 1:0.01:9;

[0052] S04, coating part of the slurry in step S03 on the surface of the carrier to obtain a coating slurry; uniformly covering the support layer on the coating slurry, and drying at 60° C. for 0.5 h to obtain a support slurry;

[0053] S05, coating the remaining slurry of step S03 on the supporting slurry of step S04, drying at 60°C for 0.5h, and then drying at 150°C for 30min, to obtain a non-fluorine proton exchange membrane for PEM water electrolysis.

[0054] In step S01,

[0055] The pretreated resin is pretreated by the following method: the resin is placed at 80° C. and dried for 24 hours under vacuum conditions to obtain the pretreated resin.

[0056] The resin is polyetheretherketone (PEEK) resin.

[0057] The molecular weight of the polyetheretherketone resin is 4000.

[0058] The drying is carried out in an oven.

[0059] The acid solution is 98wt.% concentrated sulfuric acid.

[0060] The reaction was carried out under stirring at a frequency of 500 rpm.

[0061] In step S02,

[0062] The stirring speed is 100 rpm.

[0063] The washing was performed by washing with pure water several times until the mixture became neutral.

[0064] In step S03,

[0065] The cerium salt is cerium nitrate.

[0066] The solvent is methanol.

[0067] In step S04,

[0068] The coating thickness was 400 μm.

[0069] The carrier is glass, and the surface of the glass is processed by laser engraving to form a regular groove pattern with a depth of 3 μm, a width of 2 μm, and a spacing of 2 μm.

[0070] The support layer is a porous film with a thickness of 45 μm. When covering, the porous film can be stretched through the frame to ensure that the porous film is flat, so that it can be evenly covered on the coating slurry, thereby ensuring that the coating slurry can fully infiltrate the porous film.

[0071] The support layer is composed of an ultra-fine polyetheretherketone fiber woven mesh.

[0072] The drying is achieved by means of a forced air drying oven.

[0073] In step S05,

[0074] The coating thickness is 400 μm. In the present application, the coating is achieved by a coater.

[0075] The drying and the drying are both achieved through an air blast drying oven.

[0076] The thickness of the prepared non-fluorinated proton exchange membrane for PEM water electrolysis is 50 microns; the tensile strength is 60 MPa; the elongation at break is 121%; the proton conductivity is 283 mS / cm at 80°C and 100% relative humidity; the hydrogen permeability is 0.005 mL / min·cm 2 ·atm. Tested in a PEM electrolyzer, with deionized water flowing in at 80°C, maintaining 2A / cm 2 The current density only requires an electrolysis voltage of 1.71 V. It can be seen that the prepared proton exchange membrane meets the relevant requirements for proton exchange membranes for PEM electrolyzers.

[0077] Example 2

[0078] A method for preparing a non-fluorine proton exchange membrane for PEM water electrolysis comprises the following steps:

[0079] S01, adding the pretreated resin to the acid solution, reacting at 30° C. for 8 hours to obtain a product mixed solution; the mass ratio of the pretreated resin to the acid solution is 1:10;

[0080] S02, adding the product mixture of step S01 into ice water while stirring, filtering, taking the filter residue, washing and drying to obtain the product (sulfonated polyetheretherketone, SPEEK);

[0081] S03, mixing the product of step S02, cerium salt and solvent, stirring for 6 hours and then ultrasonicating for 5 hours to obtain a slurry; the mass ratio of the product, the cerium salt and the solvent is 1:0.2:9;

[0082] S04, coating part of the slurry in step S03 on the surface of the carrier to obtain a coating slurry; uniformly covering the support layer on the coating slurry, and drying at 40° C. for 24 hours to obtain a support slurry;

[0083] S05, coating the remaining slurry of step S03 on the supporting slurry of step S04, drying at 40°C for 24 hours, and then drying at 120°C for 60 minutes to obtain a non-fluorine proton exchange membrane for PEM water electrolysis.

[0084] In step S01,

[0085] The pretreated resin is pretreated by the following method: the resin is placed at 80° C. and dried for 24 hours under vacuum conditions to obtain the pretreated resin.

[0086] The resin is polyetheretherketone (PEEK) resin.

[0087] The molecular weight of the polyetheretherketone resin is 10,000.

[0088] The drying is carried out in an oven.

[0089] The acid solution is 98wt.% concentrated sulfuric acid.

[0090] The reaction was carried out under stirring at a frequency of 1000 rpm.

[0091] In step S02,

[0092] The stirring speed is 400 rpm.

[0093] The washing was performed by washing with pure water several times until the mixture became neutral.

[0094] In step S03,

[0095] The cerium salt is cerium chloride.

[0096] The solvent is deionized water.

[0097] In step S04,

[0098] The coating thickness was 100 μm.

[0099] The carrier is glass, and the surface of the glass is processed by laser engraving to form a regular groove pattern with a depth of 3 μm, a width of 2 μm, and a spacing of 2 μm.

[0100] The support layer is a porous film with a thickness of 45 μm. When covering, the porous film can be stretched through the frame to ensure that the porous film is flat, so that it can be evenly covered on the coating slurry, thereby ensuring that the coating slurry can fully infiltrate the porous film.

[0101] The component of the support layer is expanded porous polytetrafluoroethylene.

[0102] The drying is achieved by means of a forced air drying oven.

[0103] In step S05,

[0104] The coating thickness is 100 μm. In the present application, coating is achieved by a coater.

[0105] The drying and the drying are both achieved through an air blast drying oven.

[0106] The thickness of the prepared non-fluorinated proton exchange membrane for PEM water electrolysis is 52 microns; the tensile strength is 75 MPa; the elongation at break is 112%; the proton conductivity is 223 mS / cm at 80°C and 100% relative humidity; the hydrogen permeability is 0.003 mL / min·cm 2 ·atm. Tested in a PEM electrolyzer, with deionized water flowing in at 80°C, maintaining 2A / cm 2 The current density only requires an electrolysis voltage of 1.96 V. It can be seen that the prepared proton exchange membrane meets the relevant requirements of proton exchange membranes for PEM electrolyzers.

[0107] Example 3

[0108] A method for preparing a non-fluorine proton exchange membrane for PEM water electrolysis comprises the following steps:

[0109] S01, adding the pretreated resin to the acid solution, reacting at 50° C. for 5 hours, to obtain a product mixed solution; the mass ratio of the pretreated resin to the acid solution is 1:30;

[0110] S02, adding the product mixture of step S01 into ice water while stirring, filtering, taking the filter residue, washing and drying to obtain the product (sulfonated polyetheretherketone, SPEEK);

[0111] S03, mixing the product of step S02, cerium salt and solvent, stirring for 24 hours and then ultrasonicating for 8 hours to obtain a slurry; the mass ratio of the product, the cerium salt and the solvent is 1:0.1:9;

[0112] S04, coating part of the slurry in step S03 on the surface of the carrier to obtain a coating slurry; uniformly covering the support layer on the coating slurry, and drying at 100° C. for 1 hour to obtain a support slurry;

[0113] S05, coating the remaining slurry of step S03 on the supporting slurry of step S04, drying at 100°C for 1 hour, and then drying at 200°C for 10 minutes to obtain a non-fluorine proton exchange membrane for PEM water electrolysis.

[0114] In step S01,

[0115] The pretreated resin is pretreated by the following method: the resin is placed at 80° C. and dried for 24 hours under vacuum conditions to obtain the pretreated resin.

[0116] The resin is polyetheretherketone (PEEK) resin.

[0117] The molecular weight of the polyetheretherketone resin is 30,000.

[0118] The drying is carried out in an oven.

[0119] The acid solution is 98wt.% concentrated sulfuric acid.

[0120] The reaction was carried out under stirring at a frequency of 1000 rpm.

[0121] In step S02,

[0122] The stirring speed is 400 rpm.

[0123] The washing was performed by washing with pure water several times until the mixture became neutral.

[0124] In step S03,

[0125] The cerium salt is cerium dioxide.

[0126] The solvent is acetone.

[0127] In step S04,

[0128] The coating thickness was 300 μm.

[0129] The carrier is glass, and the surface of the glass is processed by laser engraving to form a regular groove pattern with a depth of 3 μm, a width of 2 μm, and a spacing of 2 μm.

[0130] The support layer is a porous film with a thickness of 45 μm. When covering, the porous film can be stretched through the frame to ensure that the porous film is flat, so that it can be evenly covered on the coating slurry, thereby ensuring that the coating slurry can fully infiltrate the porous film.

[0131] The component of the support layer is expanded porous polybenzimidazole.

[0132] The drying is achieved by means of a forced air drying oven.

[0133] In step S05,

[0134] The coating thickness is 300 μm. In the present application, coating is achieved by a coater.

[0135] The drying and the drying are both achieved through an air blast drying oven.

[0136] The thickness of the prepared non-fluorinated proton exchange membrane for PEM water electrolysis is 50 microns; the tensile strength is 41 MPa; the elongation at break is 102%; the proton conductivity is 326 mS / cm at 80°C and 100% relative humidity; the hydrogen permeability is 0.008 mL / min·cm 2 ·atm. Tested in a PEM electrolyzer, with deionized water flowing in at 80°C, maintaining 2A / cm 2 The current density only requires an electrolysis voltage of 1.65 V. It can be seen that the prepared proton exchange membrane meets the relevant requirements of proton exchange membranes for PEM electrolyzers.

[0137] Comparative Example 1

[0138] A method for preparing a proton exchange membrane for PEM water electrolysis comprises the following steps:

[0139] S01: Fix the support layer expanded porous film to the frame in advance, and then stretch it at various places with tape to make the film bear the force evenly as much as possible;

[0140] S02: dripping perfluorosulfonic acid ester solution onto the glass plate, and controlling the coating height to be 400 μm for coating;

[0141] S03: horizontally laying the expanded porous film stretched by the frame in step S01 onto the resin solution in step S02;

[0142] S04: the semi-finished product of step S03 is transferred to a blast drying oven, the temperature is controlled to 80° C., the time is 30 minutes, and further dried;

[0143] S05: Take out the semi-finished product of S04, drip the resin solution on the semi-finished product, and control the coating height to be 400 microns for coating;

[0144] S06: Transfer the semi-finished product in S05 to a blast drying oven, control the temperature to 80°C, and dry it for 30 minutes for further drying;

[0145] S07: Control the temperature to 150 degrees, the time to 0.5 hours, and further dry to obtain a PEM proton exchange membrane for water electrolysis.

[0146] The thickness of the proton exchange membrane is 51 microns; the tensile strength is 31 MPa; the elongation at break is 138%; the proton conductivity is 181 mS / cm at 80°C and 100% relative humidity; the hydrogen permeability is 0.012 mL / min·cm 2 ·atm. Tested in a PEM electrolyzer, with deionized water flowing in at 80°C, maintaining 2A / cm 2A current density of 1.85 V is required for electrolysis.

[0147] Figure 1 and Figure 2 They are electron microscope cross-sectional views of the proton exchange membranes of Example 1 and Comparative Example 1, respectively. Figure 1 and Figure 2 By comparison, it can be seen that the cross section of the proton membrane prepared in the embodiment of the present application is dense and seamless, and the SPEEK resin is completely filled into the ultrafine polyetheretherketone fiber network, which has good interface compatibility. This is due to the fact that the support layer material uses the same main chain structure resin as the SPEEK resin, which can greatly improve the interface compatibility between the support layer and the resin, so that the obtained proton membrane has a denser structure, can provide higher mechanical strength, higher proton conductivity and better ability to block gas penetration. Comparative Example 1 is a common solution for existing commercial PEM water electrolysis proton exchange membranes. The electron microscope cross section of the proton membrane has obvious pores and fault interfaces, which makes it have many problems when used in PEM electrolyzers.

[0148] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a non-fluorinated proton exchange membrane for PEM water electrolysis, characterized in that: The steps include: S01, adding the pretreated resin into the acid solution, reacting at 30°C to 80°C for 0.5h to 8h to obtain a product mixed solution; S02, adding the product mixture of step S01 into ice water while stirring, filtering, taking the filter residue, washing and drying to obtain the product; S03, mixing the product of step S02, cerium salt and solvent, stirring for 1h to 24h and then ultrasonicating for 1h to 8h to obtain a slurry; the mass ratio of the product, the cerium salt and the solvent is 1:(0.01-0.2):9; S04, coating part of the slurry in step S03 on the surface of the carrier to obtain a coating slurry; uniformly covering the support layer on the coating slurry, and drying at 40° C. to 100° C. for 0.5 h to 24 h to obtain a support slurry; S05, coating the remaining slurry of step S03 on the supporting slurry of step S04, drying at 40°C to 100°C for 0.5h to 24h, and then drying at 120°C to 200°C for 10min to 60min to obtain a non-fluorine proton exchange membrane for PEM water electrolysis.

2. The method for preparing a non-fluorinated proton exchange membrane for PEM water electrolysis according to claim 1, characterized in that: In step S01, the pretreated resin is pretreated by the following method: drying the resin at 80° C. for 24 hours under vacuum conditions to obtain a pretreated resin; The mass ratio of the pretreatment resin to the acid solution is 1:(10-50); The resin is polyetheretherketone resin.

3. The method for preparing a non-fluorinated proton exchange membrane for PEM water electrolysis according to claim 2, characterized in that: The molecular weight of the polyetheretherketone resin is 1000-50000.

4. The method for preparing a non-fluorinated proton exchange membrane for PEM water electrolysis according to claim 1, characterized in that: In step S01, The acid solution is 98wt.% concentrated sulfuric acid; The reaction is carried out under stirring, and the stirring frequency is 500 rpm to 1000 rpm.

5. The method for preparing a non-fluorinated proton exchange membrane for PEM water electrolysis according to claim 1, characterized in that: In step S02, the stirring speed is 100 rpm to 400 rpm; the washing is performed by washing with pure water for multiple times until it becomes neutral.

6. The method for preparing a non-fluorinated proton exchange membrane for PEM water electrolysis according to claim 1, characterized in that: In step S03, The cerium salt is one or a mixture of at least two of cerium nitrate, cerium dioxide, cerium chloride and cerium sulfate; The solvent is one or a mixture of at least two of methanol, ethanol, n-propanol, isopropanol, deionized water, acetone, DMAc or DMF.

7. The method for preparing a non-fluorinated proton exchange membrane for PEM water electrolysis according to claim 1, characterized in that: In step S04, The coating thickness is 10 μm to 400 μm; The carrier is glass; The support layer is a porous film with a thickness of 5 μm to 50 μm.

8. The method for preparing a non-fluorinated proton exchange membrane for PEM water electrolysis according to claim 1, characterized in that: In step S04, The component of the support layer is preferably one or a mixture of at least two of expanded porous polytetrafluoroethylene, ultrafine polyetheretherketone fiber woven mesh, expanded porous polybenzimidazole, expanded porous polyethylene, expanded porous polyetheretherketone, expanded porous polystyrene, artificial graphite or expanded porous polyethyleneimine; The drying is achieved by means of a forced air drying oven.

9. The method for preparing a non-fluorinated proton exchange membrane for PEM water electrolysis according to claim 1, characterized in that: In step S05, The coating thickness is 10 μm to 400 μm; The drying is carried out at 50° C. to 90° C. for 2 h to 20 h; the drying is carried out at 130° C. to 180° C. for 15 min to 50 min; the drying and the drying are both carried out in a blast drying oven.

10. A non-fluorine proton exchange membrane for PEM water electrolysis, characterized in that: The non-fluorine proton exchange membrane for PEM water electrolysis is prepared by the preparation method according to any one of claims 1 to 9.